Saadi's moral lessons about tendency to the world and worldliness - Yousuf, Abbas Dawi (Al-Adab Journal, 2022)
The comprehensiveness of Saadi’s ideas and the abundance of his books, which are replete with Qur’anic verses, prophetic hadiths, and sayings of great clerics, as well as his great presence in the culture of Iranian society over the past few centuries, were the motivation and motivator for us to get to know his ideas better. The subject of the world is one of Saadi's ideas or beliefs that we must study, given its importance. This issue has always been the subject of debate among different ideas and schools, with different groups offering opinions on the subject according to their beliefs. Therefore, the importance of how to deal with the world, on the one hand, and Saadi's prestigious position in the culture of Iranian society, on the other, make us study the subject of the world in his works to know his way of thinking about it. In this article, which is conducted in a content analysis method, we explain and analyze the different aspects of the attitude of the Sheikh of Shiraz (Saadi) towards the subject of the world. What will be discussed in this research, is that Saadi has a balanced view of the world because of his influence on religious teachings and because of his unique genius; His praise of the world as well as his criticism of it, is not only a contradiction, but rather shows the balanced and fair view of Sheikh Saadi on the subject of the world.